Towards Substantive Democracy In Indonesia: A Viewpoint - Misno, I Made Gede Ray (LPPM Universitas Jambi, 2023)
Democracy is the most appropriate choice for our nation in carrying out the life of the nation and state. With democracy, the political rights of every citizen are guaranteed to be the same. Every citizen has the right to vote and be elected into political power, in contrast to monarchies where hereditary law applies. Because all citizens have the same rights and obligations in politics, democracy can only work effectively if these political positions are filled or held by people who have good qualifications, competences, and morals, so that they are able to represent people. who have given him the confidence to occupy a given political position with the aim of mutual welfare, as stated in the Preamble to the 1945 Constitution.